Grammar and composition (New York, 2001)
This is a high school textbook focusing on english writing. The contents are devided into three section Composition, Grammar, usage and mechanics and Resources and skills
Keywords: English language,Writing,English language,Tiếng Anh; Composition and exercises,Study and teaching (Middle school),Grammar,Study and teaching (Middle school),Ngữ pháp,Học và giảng dạy (Trường trung học)